Analisis Konflik Israel-Palestina Ditinjau dari Perspektif Instrumen HAM Internasional - Sifana, Firdha; Alamsyah, Fiqih Dien; Simanjuntak, Max Doan; Wahyuni, Ridha (Media Hukum Indonesia (MHI), 2024)
Human rights is a right owned by every individual on this earth that is absolute and cannot be reduced. In the international world, human rights are protected and have legal regulations, but human rights violations still often occur in individual humans, one of which in this case is Palestinian civilians. The research method used in this research is normative juridical method. The results of this study state that Israel in attacking Palestinian civilians, has ignored the 1949 Geneva convention that has been ratified by Israel. In this case, international institutions such as the UN Security Council need to take a role in mediating the conflict. However, Israel has not ratified the Rome Statute of 1998 so it is not yet the authority of the ICC to prosecute, so a referral to the UN Security Council is needed. The national law that was established because it did not ratify the 1998 Rome Statute has not achieved justice and works the other way around because it protects Israel to be tried by the ICC. In addition, in the case of wars such as the Israeli-Palestinian conflict, non-derogable rights need to be applied and should not be limited because it can be considered a violation of human rights. However, Israel ignores this right by attacking Palestinian civilians and medical personnel.